Targeted next-generation sequencing for cancer-associated gene mutation and copy number detection in 206 patients with non–small-cell lung cancer. Issue 1 (1st January 2021) - Zheng, Songbai; Wang, Xiaodan; Fu, Ying; Li, Beibei; Xu, Jianhua; Wang, Haifang; Huang, Zhen; Xu, Hui; Qiu, Yurong; Shi, Yaozhou; Li, Kui
ABSTRACT: The knowledge of genetic variation in Chinese patients with non–small-cell lung cancer (NSCLC) is still limited. We aimed to profile this genetic variation in 206 Chinese patients with NSCLC using next-generation sequencing. Tumor tissues or whole-blood samples were collected and subjected to whole-exome targeted next-generation sequencing, which included 565 tumor-associated genes, for somatic gene mutation screening and copy number variation (CNV) detection. Potential functions of most commonly mutated genes and genes with CNV were predicted by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses. Atotal of 18, 749 mutations were identified using targeted next-generation sequencing, and 85.3% of them were missense mutations. Among the mutation, conversions between pyrimidine and purine were predominant, and C> T/G > A was the most common substitution type. High frequencies of mutations were noted in TP53 (47.6%), EGFR (41.7%), CREBBP (23.1%), KMT2C (16.9%), MUC2 (16.6%), DNMT3A (15.5%), LRP1B (15.5%), MUC4 (15.5%), CDC27 (15.2%), and KRAS (12.8%). EGFR and KRAS mutations were mutually exclusive. The tumor mutation load showed differences depending on gender and tumor type. CNV analysis showed that BCORL1 and ARAF have the highest copy number amplification, whereas KDM6A and RBM10 showed the highest copy number deletion. GO and KEGG analyses indicated that high-frequency mutations and CNV genes were concentrated in tumor-related PI3K-Akt, FoxO, and Ras signaling pathway. Cumulatively, we studied somatic gene mutations involved in NSCLC and predicted their clinical significance in Chinese population. These findings may provide clues for etiology and drug target of NSCLC. GRAPHICAL ABSTRACT: